New (benz)imidazolopyridino tacrines as nonhepatotoxic, cholinesterase inhibitors for Alzheimer disease. (May 2017) - Boulebd, Houssem; Ismaili, Lhassane; Martin, Helene; Bonet, Alexandre; Chioua, Mourad; Marco Contelles, José; Belfaitah, Ali
Aim : Due to the multifactorial nature of Alzheimer's disease, there is an urgent search for new more efficient, multitarget-directed drugs.Results : This paper describes the synthesis, antioxidant and in vitro biological evaluation of ten (benz)imidazopyridino tacrines (7–16 ), showing less toxicity than tacrine at high doses, and potent cholinesterase inhibitory capacity, in the low micromolar range. Among them, compound10 is a nonhepatotoxic tacrine at 1000 mM, showing moderate, but totally selective electric eel acetylcholinesterase inhibition, whereas molecule16 is twofold less toxic than tacrine at 1000 μM, showing moderate and almost equipotent inhibition for electric eel acetylcholinesterase and equine butyrylcholinesterase.Conclusion: (Benz)imidazopyridino tacrines (7–16 ) have been identified as a new and promising type of tacrines for the potential treatment of Alzheimer's disease.